Beneficial Changes in Growth Performance, Antioxidant Capacity, Immune Response, Hepatic Health, and Flesh Quality of Trachinotus ovatus Fed With Oedocladium carolinianum - Zhao, Wei; Cui, Xin; Wang, Zi-Qiao; Yao, Rong; Xie, Shi-Hua; Gao, Bao-Yan; Zhang, Cheng-Wu; Niu, Jin (Frontiers in Immunology, 2022)
The purpose of this study is to assess the feasibility of astaxanthin-rich Oedocladium carolinanum as an immunostimulant in the diet for Trachinotus ovatus. Three experimental diets containing 0% (OC0), 1% (OC1) and 5% (OC5) O. carolinanum powder were formulated for 6-week feeding trials. The results indicated that the OC5 diet boosted the growth performance through decreasing feed conversion ratio and increasing digestive enzyme activities and intestinal villi length. Meanwhile, fish fed with OC5 diet promoted antioxidant ability via stimulating the Nrf2-ARE signal pathway and enhancing antioxidant enzymes activities. Furthermore, OC5 diet exerted the hepatoprotective effects by suppressing lipid deposition and inflammation response and enhancing the transport capacity of cholesterol, and improved the non-specific immunity by activating lysozyme and complement system and increasing the nitric oxide content and total nitric oxide synthase activity. Besides, dietary O. carolinanum supplementation promoted the deposition of astaxanthin in the whole body. Therefore, a diet supplemented with 5% O. carolinanum is recommended to boost the growth, antioxidant capacity, immune response, and flesh quality of T. ovatus.